Should we treat severe vasovagal syncope with a pacemaker?. (14th March 2017) - Sutton, R.
Abstract: Cardiac pacing for vasovagal syncope (VVS) addresses the cardioinhibitory component of the reflex but cannot directly affect vasodepression, which occurs in every reflex even when hidden by dominant cardioinhibition. The randomized controlled trials of pacing in VVS have, after almost 2 decades, determined that a small number of patients can benefit because their vasodepressor component is not severe. Early studies compared pacing with no therapy yielding highly significant benefits. Subsequently, all study patients had implanted devices with half being switched off. No benefit was seen. The ISSUE‐3 study found significant benefit ( P < 0.039) in prevention of syncope recurrence in older patients. A sub‐study later showed those with negative tilt tests, otherwise indistinguishable from tilt‐positives, had 5% recurrence in 21 months ( P < 0.004). There is acceptance that pacing must be dual chamber, but the question of how pacing is delivered remains open. Relying on falling heart rate is insufficient, probably because it occurs too late. Other algorithms which indirectly detect neuroendocrine changes earlier than heart rate fall may have useful application. In clinical terms, the patient to be considered for pacing should not be young and have severe symptoms. Ideally, tilt testing should be negative implying vasodepression of lesser severity and, therefore, yielding fewer syncope recurrences. When selecting pacing, additional concern must be given to regression to the mean of symptoms, severe to less severe. Patients seek help when they are at their worst. Moreover, many years of pacing are unlikely to be free of complications related to implanted hardware.